Land Use Prediction Using Markov Cellular Automata in the Peusangan Watershed, Aceh - Fitri*, Rini; Damayanti, Astrid; Simangunsong, Nur Intan; Munawir, Munawir (Graduate School of Universitas Syiah Kuala, 2022)
The population growth rate is a factor that causes changes in land use that impact land ecology due to increased population activities related to social, economic, and cultural aspects. Land use change aims to develop facilities and infrastructure to meet the population's needs. This research seeks to interpret land-use changes in 1999, 2008, and 2019 and predict land use in the Peusangan watershed in 2030. The map overlay method analyzes land use change in 1999-2008, 2008-2019, and 2019-2030. In predicting land use, this study uses the Cellular Automata approach. The results of the analysis specifically show that the trend of land use change until 2030 is a decrease in the area of forest land use covering an area of 11,014 ha (4.27%), open land covering an area of 31 ha (0.01%), shrubs 6,083 ha (2.36%), and water bodies covering an area of 459 ha (0.18%). On the other hand, it is predicted that in 2030 the Peusangan watershed will see the most significant increase in land use for plantations of 14,225 ha (5.52%), followed by land use of 1,664 ha (0.65%), 817 ha (0.32%), settlements covering 710 ha (0.28%), 132 ha of rice fields (0.05%), and 28 ha of pond land use (0.01%). The results of this study are expected to be input for policymakers regarding land use planning in the Peusangan watershed in the future.